RETRACTED ARTICLE: The Notch signal mediates macrophage polarization by regulating miR-125a/miR-99b expression - Qian Li; Xia He; Qiao Yu; Yuan Wu; Mingyu Du; Jing Chen; Fanyu Peng; Wenjun Zhang; Jie Chen; Yan Wang; Hanbo Chen; Hairong Wang; et al. (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editor, Publisher, and Authors of Artificial Cells, Nanomedicine and Biotechnology, have retracted the following article:Qian Li, Xia He, Qiao Yu, Yuan Wu, Mingyu Du, Jing Chen, Fanyu Peng, Wenjun Zhang, Jie Chen, Yan Wang, Hanbo Chen, Hairong Wang, Dan He & Qiang Wang. (2019). The Notch signal mediates macrophage polarization by regulating miR-125a/miR-99b expression. Artificial Cells, Nanomedicine, and Biotechnology. 47:1, 833-843, DOI: 10.1080/21691401.2019.1576711We are now cognizant that substantially similar images from this article were first published in Cancer Research. When asked, the Authors were cooperative and confirmed that the wrong images had been submitted. Further internal investigation of this article also revealed issues with the rigor of the editorial process, and therefore we have collectively agreed to retract the article.We have been informed in our decision-making by the guidance of COPE guidelines on retractionsThe retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.